Imaginative Enrichment Produces Higher Preference for Unusual Music Than Historical Framing: A Literature Review and Two Empirical Studies - Chmiel, Anthony; Schubert, Emery (Frontiers in Psychology, 2020)
Does accompanying information (“framing”) such as in a program note influence our preference for music? To date the findings have been mixed, although a small body of research has suggested that when framing accompanies music considered unusual (characterized by extreme complexity, extreme unfamiliarity, and the like) the music may be preferred compared to when no such framing occurs. A literature review (Study 1) revealed that for 50% of experiments where valenced framing (positive versus negative suggestions of prestige, and the like) was manipulated, positive framing was accompanied by significantly higher ratings of preference and/or quality. However, only one example contained music that could be considered unusual (atonal music). We therefore conducted two follow-up experiments, with each examining the influence of valenced framing as well as historical framing (accompanying historical details) for music intended to be unusual. Study 2 manipulated framing for an excerpt of atonal music, although we were unable to find evidence that positively valenced historical framing increased preference for this piece. A surprising finding in Study 2 was that our active control—requiring the participant to engage imaginatively with the music—produced a significant increase in preference. Subsequently, in Study 3 we examined the same three framing conditions, and included both an unusual excerpt (free jazz) as well as an over-familiar, typical excerpt for comparison (being a repeatedly pre-exposed classical piano piece). Study 3 produced no significant differences in preference ratings between the two historical conditions, although a positive impact of imagination was again evident. Based on the results of our findings, as well as those observed in the existing literature, we concluded that the impact of historical framing may be highly subjective and not of favorable consequence to the typical listener. Furthermore, while imaginative engagement appears a fruitful avenue for further preference research, it has been largely ignored.